Ultrasensitive colorimetric DNA detection using a combination of rolling circle amplification and Nicking Endonuclease-Assisted Nanoparticle Amplification (NEANA) - Xu, Wei (2013)
A combination of rolling circle amplification and nicking endonuclease-assisted nanoparticle amplification (NEANA) is used for the rapid, colorimetric detection of DNA. The integration of rolling circle amplification into the NEANA approach allows for detection of oligonucleotides with arbitrary sequences at ultralow concentrations.